Saving the questionnaire periodontally compromised teeth in the aesthetic zone: a case report - Kamil, Wisam Alaa; Hussin, Akbar Sham (2014)
Introduction: The persistence of bleeding periodontal pockets that associated with intra-bony defects (IBD) increases the risk of tooth loss and is considered a clinical challenge. The prognosis of such teeth with grade II mobility and severe attachment loss (AL) is questionable according to McGuire 1991. Nevertheless proper periodontal treatment (PT) and supportive periodontal care might retain the periodontally compromised teeth.